A Single Switch Parallel Quasi Resonant Converter Topology for Induction Heating Application - V. Geetha; V. Sivachidambaranathan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In this paper 32 KHZ Single phase Single switch Parallel Resonant converter topology (SSPR) using power MOSFET is simulated using MATLAB simulink for the different duty cycle and the THD, Power with respect to change in duty cycle is compared . The workingcoil is the combination of R, L in parallel with C which produces the output power of 1.7KW to 3KW with variation in duty cycle at higher value in duty cycle we get less THD and more power. The operating frequency is selected nearer to the resonant frequency for the improvement performance. The experimental set up of this SSPR Inverter in the induction heating application for the domestic purpose is implemented is depicted and this validates the implementation of quasi resonant using IGBT for domestic applications.